DESIGN OF SIMPLE ELECTRICAL GENERATOR AS HIGH SCHOOL LEARNING MEDIA - Syarifah Muthia Putri; Zulkifli Bahri; Dina Maizana (AMALIAH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
Electrical energy has an important role in human life today. Many aspects of human life today rely on electrical energy. National electrical energy defense is an important issue so that Indonesia can become an independent nation in the field of electrical energy sources. Strategies in realizing this issue can be implemented by fostering the interests and talents of upper secondary level students so that the students will explore the field of electricity science. Training on simple electricity generation was conducted for students of Budi Utomo Binjai Private Vocational School so that the students could improve their skills and insight on electricity. The training was carried out by providing an understanding of the role and condition of current electricity, the design of a simple electric power plant, and providing insights on renewable energy. The results of the design during the training are given to the school which can be used as a medium of learning for students in the future. Based on the results of the questionnaire given to students during training it can be seen that 61% of the total number of students participating in training activities can have sufficiently good skills in designing simple electric power plants.